YOUTH PEOPLE’S CIVIC AND POLITICAL ENGAGEMENT AT SMAN 1 GIRI, BANYUWANGI REGENCY - Keban, Philipus; Irianto, Jusuf; Suaedi, Falih; Supeno, Eko; Wardiyanto, Bintoro; Sunaryo, Sunaryo; Mardiyanta, Antun; Supramudyo, Gitadi Tegas; Triana, Rochyati Wahyuni; Setijaningrum, Erna; Asmorowati, Sulikah; Haryono, Nanang; Ferdian, Putu Aditya; Soegiono, Agie Nugroho; Hariani, Nurul Jamila (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
This community service activity aims to increase the political and civil literacy of novice voters in preparation for the 2024 Simultaneous Elections in Indonesia. The targets of this community service activity are school students or youth who are at least 17 years old in the year the 2024 Simultaneous Election will be held. Youth were chosen as the main target because they are a group with a large proportion in the 2024 election contestation which will determine the future of democracy. As new voters, they need preparation and a deep understanding of how to participate in the political process effectively to determine the direction and policies of government. For this reason, the Public Administration Department of Universitas Airlangga will partner with the East Java Provincial Education Office which will later provide guidance to the SMAN 1 Giri, Banyuwangi Regency to hold a community service program at the school. Community service activities will involve understanding the political system, democratic processes, political issues, and the importance of active political participation. Activities will be carried out through three main stages: preparation, implementation and evaluation. The preparatory stage involves collecting and compiling relevant political and civic literacy materials. Next, the implementation stage will involve counseling, workshops and group discussions to provide in-depth understanding to novice voters. The evaluation stage will be carried out to measure the effectiveness of the program and obtain feedback from participants. It is hoped that this activity will provide a fundamental contribution in increasing the political and civil literacy of novice voters. With a better understanding of the political system, first-time voters will be able to make good political decisions, participate actively in the political process, and critically evaluate the information they receive.